Biology and morals in man's reactivity - D'Onofrio, Felice (Medicina e Morale, 1991)
The ability to react, which is present in ali animai species, is in man a dominant quality and characterizes him in all his relationships with others. In the realm of behavior the influence of hormones and their influence on the psyco-intellect of the individual must always be taken into consideration. However, the moral component of an individual which is also clearly influenced by culture, the environment and by education, as well as by the progress and communication networks of our times is also equally important. Within the same individual there are mechanisms of balance; when this balance is not achieved an illness develops that may be expressed in neurosis or other psyco-emotional disturbances. In the constant search for balance the values of trascendence should be highlighted which undoubtedly represent the most valid basis for resetting the balance of man's ability to react.